A novel dual‐band slot‐ring array antenna using both‐sided MIC technology for polarization detection. Issue 11 (30th August 2022) - Hossain, Md. Azad; Murshed, Abu Hena; Rahman, Muhammad Asad; Nishiyama, Eisuke; Toyoda, Ichihiko
Abstract: This article proposes a novel dual‐band orthogonal polarized slot‐ring array antenna for linear polarization discrimination. The array antenna is made up of 12 slot‐ring antenna elements and a slot‐ring direct detector. Four diodes are mounted on the slot‐ring detector for the direct amplitude detection of the received signal. The array antenna elements can discriminate the vertical and horizontal received signal at 7.5 GHz. The slot‐ring detector performs as an amplitude detector and has the ability to discriminate the vertical and horizontal polarization around at 5.5 GHz. The proposed antenna is tested experimentally to validate the performance and it meets the desired requirements for the polarization discrimination. The Both‐Sided MIC technology is utilized successfully for realizing the proposed slot‐ring array antenna. The advance design system (ADS) is utilized to the carry out the simulation of the proposed slot‐ring array antenna.